2005
DOI: 10.1089/ten.2005.11.567
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Neovascularization: Contributions from Bioengineering

Abstract: A number of pathological entities and surgical interventions could benefit from therapeutic stimulation of new blood vessel formation. Although strategies designed for promoting neovascularization have shown promise in preclinical models, translation to human application has met with limited success when angiogenesis is used as the single therapeutic mechanism. While clinical protocols continue to be optimized, a number of exciting new approaches are being developed. Bioengineering has played an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 136 publications
(131 reference statements)
0
52
0
Order By: Relevance
“…As host-vessel ingrowth requires a finite time to penetrate into the depth of the implanted tissue, necrosis can occur prior to sufficient vascularization, resulting in implant failure. Many studies have explored means to facilitate bioengineered angiogenesis [106,107] and ongoing in vitro attempts to prevascularize engineered tissue may have a future in in vivo applications [104,[108][109][110]. Notably, one study has already demonstrated evidence of angiogenesis in vivo attributed to multi-cell type co-culture [111].…”
Section: Ongoing Challenges In Whole-organ Engineeringmentioning
confidence: 99%
“…As host-vessel ingrowth requires a finite time to penetrate into the depth of the implanted tissue, necrosis can occur prior to sufficient vascularization, resulting in implant failure. Many studies have explored means to facilitate bioengineered angiogenesis [106,107] and ongoing in vitro attempts to prevascularize engineered tissue may have a future in in vivo applications [104,[108][109][110]. Notably, one study has already demonstrated evidence of angiogenesis in vivo attributed to multi-cell type co-culture [111].…”
Section: Ongoing Challenges In Whole-organ Engineeringmentioning
confidence: 99%
“…The ability to therapeutically control new blood vessel formation (neovascularization) could palliate a number of pathological entities and augment surgical interventions [166]. The genes of naturally occurring growth factors have been investigated as neovascularization stimuli for treatment of ischemic tissues, to promote microvascular network formation in engineered tissues, and to improve the function and survival of transplanted cells and tissues.…”
Section: Therapeutic Neovascularizationmentioning
confidence: 99%
“…Multiple growth factors act in a coordinated fashion to modulate invasion, network formation, and maturation of microvascular networks [166]. Many of the genes of the following proteins have been investigated as neovascularization therapies, including vascular endothelial growth factor (VEGF) [170], fibroblast growth factor-1 (FGF-1, or acidic FGF) [171], FGF-2 (also known as basic FGF) [172], FGF-4 [173], placental growth factor (PlGF) [174], angiotensin-1 (Ang-1) [175], and hepatic growth factor (HGF) [176].…”
Section: Therapeutic Neovascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to provide oxygen and nutrients to cells contained in biomaterial constructs have met with varying degrees of success. Engineering a tissue of clinically relevant magnitude requires the formation of extensive and stable microvascular networks within the tissue (Brey et al, 2005). Since most in vitro engineered tissue constructs do not contain the intricate microvascular structures of native tissue, the cells contained in scaffolds heavily rely on simple diffusion for oxygenation and nutritional delivery.…”
Section: Introductionmentioning
confidence: 99%